Influence of oxygen concentration on the fresh and internal cooked color of modified atmosphere packaged dark-cutting beef stored under chilled and superchilled conditions. (June 2022) - Yang, Xiaoyin; Zhang, Yi; Luo, Xin; Zhang, Yimin; Zhu, Lixian; Xu, Baochen; Hopkins, David L.; Liang, Rongrong
Abstract: The current research evaluated the combined effect of oxygen concentration (20%, 50% and 80% O2 ) and storage temperature (4°C or −1.5°C) on the fresh and internal cooked color of dark-cutting (DC) beef. Steaks were packaged in modified atmosphere packaging (MAP) over a 12-day storage period. Although the metmyoglobin reducing activity (MRA) of DC steaks decreased with increasing O2 levels, lower oxygen consumption (OC) and deeper oxygen penetration depth (OPD) improved the surface color of 50%O2 -MAP and 80%O2 -MAP DC steaks. 80%O2 -MAP resulted in the highest ( P < 0.05) percentage myoglobin denaturation and alleviated the phenomenon of persistent pink (PP) observed in DC beef. Compared with normal chilling, superchilling significantly increased the redness values of DC steaks through inhibition of lipid oxidation and enhancement of MRA, while it had no effects on PP due to the limited OPD. The results suggest that 80%O2 -MAP combined with superchilling can be used to improve fresh color and minimize PP of DC beef. Highlights: 50%O2 -MAP and 80%O2 -MAP effectively improved the surface color of DC steaks. 80%O2 -MAP relieved the development of persistent pinking (PP) in cooked DC steaks. Superchilled beef had higher MRA and redness, but lower TBARS than chilled beef. Superchilling did not improve the PP of DC steaks due to the limited OPD.